Angle recession glaucoma: A case report and review of the literature - Sharma, Rishi; Rao, Bhavaraj Veerabhadhra (Indian Journal of Case Reports, 2020)
Ocular trauma is an important cause of visual loss and has varied manifestations. Here, we present the case of a 34-year-old male who presented with a history of trauma in the right eye (RE) 2 months when he was hit with a tennis ball while playing cricket. He had a visual acuity of counting fingers close to face in the RE. The slit-lamp evaluation revealed a hyphema of more than half of the anterior chamber volume. The left eye (LE) was normal. Intraocular pressure (IOP) was 48 mmHg (RE) and 17 mmHg (LE). The patient was started on anti-glaucoma medications (tablet Diamox, eye drop Timolol, and Brimonidine) and IOP reduced to 21 mmHg in the RE. After 1 month, the gonioscopic evaluation revealed an angle recession in 4 clock hours. Recorded IOP was 18 mmHg in the RE and 16 mm Hg in the LE. The optical coherence tomography retinal nerve fiber layer showed early glaucomatous changes. Based on these findings, the patient has been diagnosed as a case of angle recession glaucoma RE and kept on follow-up.